Integration of Baduy Ecological Philosophy and Environmental Stewardship as a Model of Sustainable Environmental Ethics in Christian Education - Amirrudin Zalukhu (Program Pascasarjana UKIM, 2025)
The Baduy community upholds an ecological philosophy that emphasizes harmony with nature, reflected in their prohibitions against excessive exploitation and their respect for maintaining a balance in the ecosystem. This principle aligns with the concept of environmental stewardship in Genesis 1:26-28, which underscores humanity’s responsibility to manage the earth wisely. Integrating these two perspectives can serve as a model for sustainable ecological ethics in Christian education. This study employs a theological and ethnographic approach to explore the alignment between Baduy ecological wisdom and biblical principles. The findings reveal that this model can enrich Christian education by fostering an eco-theological awareness that balances dominion over creation with responsibility for it. By adopting Baduy sustainability principles, Christian education can promote a more inclusive and contextually relevant ecological mindset among learners. This integration offers an ethical solution to the environmental crisis, emphasizing that Christian faith must be manifested in sustainable ecological practices.